IMPACT OF COVID-19 ON AIR QUALITY: EVIDENCE FROM THE TEN MAJOR CITIES WORLD WIDE - Dr. Sugandha Chhibber (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
Air pollution constitutes the most pressing environmental health risk facing our global population. It is estimated to contribute toward 7 million premature deaths a year, while 92% of the world’s population is estimated to breathe toxic air quality (WHO, 2016). In less developed countries, 98% of children under five breathe toxic air. As a result, air pollution is the main cause of death for children under the age of 15, killing 600,000 every year (WHO, 2018). In financial terms, premature deaths due to air pollution cost about $5 trillion in welfare losses worldwide (The World Bank, 2016). Worldwide ambient air pollution accounts for 29% of all deaths and disease from lung cancer, 17% of all deaths and disease from acute lower respiratory infection, 24% of all deaths from stroke, 25% of all deaths and disease from ischaemic heart disease, 43% of all deaths and disease from chronic obstructive pulmonary disease. But despite this, the awareness regarding air pollution has remained low in the areas where real time monitoring is limited but pollution level may be high